2001
DOI: 10.3168/jds.s0022-0302(01)74476-1
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities and Correlations Among Body Condition Scores, Production Traits, and Reproductive Performance

Abstract: The objectives of this study were to estimate the heritability of body condition scores (BCS) from producer and consultant-recorded data and to describe the genetic and phenotypic relationships among BCS, production traits, and reproductive performance. Body condition scores were available at calving, postpartum, first service, pregnancy check, before dry off, and at dry off from the Dairy Records Management Systems in Raleigh, NC, through the PCDART program. Heritabilities, genetic correlations, and phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
87
2
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 22 publications
22
87
2
6
Order By: Relevance
“…The results presented generally correspond with the findings estimated by various authors in other populations. In the study by Dechow et al (2001), the estimated heritabilities for milk production in the first and second lactations were 0.29 and 0.17, respectively, which is generally close to the results estimated by Dal Zotto et al (2007) in Italian Brown Swiss (0.15). Our result of 0.20 for MLK, however, is also closer to the estimate of Dechow et al (2001) published for cows on the second lactation.…”
Section: Heritabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…The results presented generally correspond with the findings estimated by various authors in other populations. In the study by Dechow et al (2001), the estimated heritabilities for milk production in the first and second lactations were 0.29 and 0.17, respectively, which is generally close to the results estimated by Dal Zotto et al (2007) in Italian Brown Swiss (0.15). Our result of 0.20 for MLK, however, is also closer to the estimate of Dechow et al (2001) published for cows on the second lactation.…”
Section: Heritabilitysupporting
confidence: 88%
“…In the study by Dechow et al (2001), the estimated heritabilities for milk production in the first and second lactations were 0.29 and 0.17, respectively, which is generally close to the results estimated by Dal Zotto et al (2007) in Italian Brown Swiss (0.15). Our result of 0.20 for MLK, however, is also closer to the estimate of Dechow et al (2001) published for cows on the second lactation. Very low heritabilities of 0.09 for fat production and of 0.13 for protein production were estimated by Dal Zotto et al (2007) compared to our estimates of 0.21 and 0.23, respectively.…”
Section: Heritabilitysupporting
confidence: 88%
“…In Canadian Holsteins, Jamrozik et al (2005) reported 0.10 and 0.07, and Sun et al (2009) (2005) were 0.03 each. Other published heritability estimates for FLI1 ranged from 0.03 to 0.04 (Dechow et al, 2001;Wall et al, 2003). Our estimates of within-herd heritability for fertility traits in the second lactation (Table 3) were lower (CFI2 0.03, DO2 0.04, FLI2 0.02) than those in the first lactation.…”
Section: Heritabilitymentioning
confidence: 52%
“…The negative genetic correlations increased with the progressing lactation; from r g = -0.33 after calving to r g = -0.50 on day 240. Dechow et al (2001) also reported the negative relationship between BCS and milk yield, which was characterized by the estimated value of r g ; it ranged from -0.27 to -0.31.…”
Section: Resultsmentioning
confidence: 95%
“…The results of these studies are inconsistent in the reported relationship between BCS and milk yield. Some authors determined genetic correlations between these traits as slightly negative (Berry et al, 2002;Pryce et al, 2002), whereas others found slightly positive correlations (Dechow et al, 2001).…”
mentioning
confidence: 99%